VD_FINDINFO HC / 2025 / 577 vom 11. August 2025 - VD Tribunal cantonal (2025)
REJET DE LA DEMANDE, REVENU HYPOTHÉTIQUE, GARDE ALTERNÉE, DÉBITEUR, DIRECTIVEINJONCTION | 176 al. 1 ch. 1 CC, 176 al. 1 ch. 3 CC, 285 CC, 298 CC